EmCyclinD-EmCDK4/6 complex is involved in the host EGF-mediated proliferation of Echinococcus multilocularis germinative cells via the EGFR-ERK pathway - Feng, Chonglv; Cheng, Zhe; Xu, Zhijian; Tian, Ye; Tian, Huimin; Liu, Fan; Luo, Damin; Wang, Yanhai (Frontiers in Microbiology, 2022)
The larval stage of the tapeworm Echinococcus multilocularis causes alveolar echinococcosis (AE), one of the most lethal helminthic infections in humans. The tumor-like growth and development of the metacestode larvae within host organs are driven by a population of somatic stem cells, the germinative cells, which represent the only proliferative cells in the parasite. Host-derived factors have been shown to promote germinative cell proliferation. Since cells sense the external signal mainly in G1 phase of the cell cycle, host factors are expected to exert impacts on the machinery regulating G1/S phase of the germinative cells, which still remains largely unknown in E. multilocularis. In this study, we described the characterization of two key members of the G1/S phase cell-cycle regulation, EmCyclinD and EmCDK4/6. Our data show that EmCyclinD and EmCDK4/6 display significant sequence similarity to their respective mammalian homologues, and that EmCyclinD interacts with EmCDK4/6, forming a kinase-active complex to activate its substrate Rb1. EmCyclinD was actively expressed in the germinative cells. Addition of human EGF caused an elevated expression of EmCyclinD while inhibition of the EGFR-ERK signaling pathway in the parasite reduced the expression of EmCyclinD and downstream transcriptional factors. Treatment with Palbociclib, a specific CDK4/6 inhibitor, downregulated the expression of cell cycle-related factors and impeded germinative cell proliferation and vesicle formation from protoscoleces. Our data demonstrated that the EmCyclinD-EmCDK4/6 complex participates in the cell cycle regulation of germinative cells which is mediated by host EGF via the EGFR-ERK-EmCyclinD pathway in E. multilocularis.